Ring trial of 2nd generation RT‐QuIC diagnostic tests for sporadic CJD. Issue 11 (13th November 2020) - Orrú, Christina D.; Groveman, Bradley R.; Foutz, Aaron; Bongianni, Matilde; Cardone, Franco; McKenzie, Neil; Culeux, Audrey; Poleggi, Anna; Grznarova, Katarina; Perra, Daniela; Fiorini, Michele; Liu, Xiaoqin; et al.
Abstract: Objective: Real‐time quaking‐induced conversion (RT‐QuIC) assays detect prion‐seeding activity in a variety of human biospecimens, including cerebrospinal fluid and olfactory mucosa swabs. The assay has shown high diagnostic accuracy in patients with prion disorders. Recently, advances in these tests have led to markedly improved diagnostic sensitivity and reduced assay times. Accordingly, an algorithm has been proposed that entails the use of RT‐QuIC analysis of both sample types to diagnose sporadic Creutzfeldt‐Jakob disease with nearly 100% accuracy. Here we present a multi‐center evaluation (ring trial) of the reproducibility of these improved "second generation" RT‐QuIC assays as applied to these diagnostic specimens. Methods: Cerebrospinal fluid samples were analyzed from subjects with sporadic Creutzfeldt‐Jakob ( n = 55) or other neurological diseases ( n = 45) at multiple clinical centers. Olfactory mucosa brushings collected by multiple otolaryngologists were obtained from nine sporadic Creutzfeldt‐Jakob disease cases and 19 controls. These sample sets were initially tested blindly by RT‐QuIC by a coordinating laboratory, recoded, and then sent to five additional testing laboratories for blinded ring trial testing. Results: Unblinding of the results by a third party indicated 98‐100% concordance between the results obtained by the testing of these cerebrospinal fluid and nasal brushings at the six laboratories. Interpretation: This second‐generation RT‐QuIC assay is highly transferrable, reproducible, and therefore robust for the diagnosis of sporadic Creutzfeldt‐Jakob disease in clinical practice.